Haematobiochemical Changes In Sheep And Goats During Natural Infection Of Haemonchus Contortus - kumari, Suchita; Sinha, S. R. P.; Sinha, Sucheta (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Various haemato-biochemical parameters were estimated during natural haemonchosis in sheep and goats . Significant decrease in the values of haemoglobin percentage, total erythrocyte counts, packed cell volume, lymphocyte percentage, blood glucose and total serum protein values were observed in infected animals; whereas erythrocyte sedimentation rate, total leucocytic counts, neutrophil and eosinophil percentages were increased significantly both in case of infected sheep and goats. Significant rise was also observed in the values of SGOT and SGPT during haemonchosis in both animals.